2016
DOI: 10.1371/journal.pone.0164257
|View full text |Cite
|
Sign up to set email alerts
|

Health Status of Sand Flathead (Platycephalus bassensis), Inhabiting an Industrialised and Urbanised Embayment, Port Phillip Bay, Victoria as Measured by Biomarkers of Exposure and Effects

Abstract: Port Phillip Bay, Australia, is a large semi-closed bay with over four million people living in its catchment basin. The Bay receives waters from the Yarra River which drains the city of Melbourne, as well as receiving the discharges of sewage treatment plants and petrochemical and agricultural chemicals. A 1999 study demonstrated that fish inhabiting Port Phillip Bay showed signs of effects related to pollutant exposure despite pollution management practices having been implemented for over a decade. To asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…www.mdpi.com/journal/metabolites Sand flathead (Platycephalus bassensis) is a suitable sentinel species for ecotoxicological investigations in Port Phillip Bay as it is sedentary, non-migratory, and positioned high in the food chain [25,26] and has been used previously as an indicator of the pollution status of Port Phillip Bay [26,27] and in Tasmania [28,29]. Other findings have already been published on the same cohort of fish presented in this study, whereby tissue contaminant concentrations, a range of physiological indicators, and biomarkers of fish health demonstrate that sand flathead are still exposed to and exhibit the effects of low level contaminants in some parts of the Bay [21,30,31]. More specifically, whilst PAH, PCB, and OC concentrations were all below detection in edible muscle, some metals, in particular Hg, were detected (Table 1), albeit at levels below Australian Food Standards guideline values [21].…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…www.mdpi.com/journal/metabolites Sand flathead (Platycephalus bassensis) is a suitable sentinel species for ecotoxicological investigations in Port Phillip Bay as it is sedentary, non-migratory, and positioned high in the food chain [25,26] and has been used previously as an indicator of the pollution status of Port Phillip Bay [26,27] and in Tasmania [28,29]. Other findings have already been published on the same cohort of fish presented in this study, whereby tissue contaminant concentrations, a range of physiological indicators, and biomarkers of fish health demonstrate that sand flathead are still exposed to and exhibit the effects of low level contaminants in some parts of the Bay [21,30,31]. More specifically, whilst PAH, PCB, and OC concentrations were all below detection in edible muscle, some metals, in particular Hg, were detected (Table 1), albeit at levels below Australian Food Standards guideline values [21].…”
Section: Introductionsupporting
confidence: 68%
“…All fish were processed within 2 h of capture and killed by iki jime [59]. Fish were individually examined for external parasites or anomalies, morphological parameters (weight, length, liver weight, carcass weight) were recorded, condition factor (CF) and liver somatic index (LSI) were calculated from these parameters, and a suite of biopsies were collected (as described in Baker et al [30]). Several biochemical markers (biliary PAH metabolites, EROD activity, liver carboxylesterase, oxidative DNA damage) have been reported in Baker et al [30]; liver gene expression and liver histology have been reported in Fu et al [31]; while contaminant levels in the flesh of these fish have been reported in Gagnon et al [21].…”
Section: Fish Collection and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…For s‐SDH measurements, serum samples (50 µl) were placed in a cuvette with 450 µl of 0.1 M Tris Buffer pH 7.5, and incubated for 10 min at room temperature to allow the formation of keto acids in the serum. Thereafter, 100 µl of 4 M fructose solution was added to the cuvette and the rate of the decrease in absorbance (340 nm) over 1 min was immediately measured using a Hitachi U‐2000 spectrophotometer as described in Baker et al (2016) . The final SDH activity is expressed as milli‐International Units (mIU) per ml serum, where 1 mIU is the amount of enzyme that will convert 1 nM of substrate per minute.…”
Section: Methodsmentioning
confidence: 99%
“…The EROD activity was assessed by the fluorimetric method as described by Webb and Gagnon (2013). 9 16 The final SDH activity is expressed…”
Section: Ethoxyresorufin-o-deethylase (Erod) Activity Measurementmentioning
confidence: 99%